Energetic Oxygen and Sulfur Charge States in the Outer Jovian Magnetosphere: Insights From the Cassini Jupiter Flyby. Issue 21 (8th November 2019) - Allen, R. C.; Paranicas, C. P.; Bagenal, F.; Vines, S. K.; Hamilton, D. C.; Allegrini, F.; Clark, G.; Delamere, P. A.; Kim, T. K.; Krimigis, S. M.; Mitchell, D. G.; Smith, T. H.; et al.
Abstract: On 10 January 2001, Cassini briefly entered into the magnetosphere of Jupiter, en route to Saturn. During this excursion into the Jovian magnetosphere, the Cassini Magnetosphere Imaging Instrument/Charge‐Energy‐Mass Spectrometer detected oxygen and sulfur ions. While Charge‐Energy‐Mass Spectrometer can distinguish between oxygen and sulfur charge states directly, only 95.9 ± 2.9 keV/ e ions were sampled during this interval, allowing for a long time integration of the tenuous outer magnetospheric (~200 RJ ) plasma at one energy. For this brief interval for the 95.9 keV/ e ions, 96% of oxygen ions were O +, with the other 4% as O 2+, while 25% of the energetic sulfur ions were S +, 42% S 2+, and 33% S 3+ . The S 2+ /O + flux ratio was observed to be 0.35 (±0.06 Poisson error). Plain Language Summary: While en route to Saturn, Cassini received a gravity assist from Jupiter. During this Jupiter flyby, Cassini briefly entered into the Jovian magnetosphere, due to an especially extended period of low solar wind pressure. In this paper, we focus on observations of the relative flux abundance of energetic (95.9 keV/ e ) heavy ions (oxygen and sulfur) by ion charge state (i.e., O n+ and S n+ ). These heavy ions would have largely originated from the moon Io, located 5.9 Jupiter radii (RJ ) from Jupiter, while the observations from Cassini are near 200 RJ . By comparing the relative charge state zabundances of these heavy ions in the outer magnetosphere to previous observations closer to Io, we can study the evolution of plasma as it is transported away from Jupiter. These observations also serve to constrain modeling efforts and provide context to instruments incapable of independent ion mass and charge state determination. Key Points: Cassini measured the relative charge state abundances of 95.9 keV/ e oxygen and sulfur in the outer magnetosphere (~200 RJ ) of Jupiter The flux of 95.9 keV/ e O + was higher than that of S 2+, with S 2+ being the most abundant charge state among sulfur ions The relative abundances of 95.9 keV/ e heavy ions are compared to thermal ions in the inner to middle magnetosphere